2016
DOI: 10.3892/etm.2016.3537
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in interventional therapy of patients with acute myocardial infarction prior to and after treatment

Abstract: The aim of the study was to investigate the cardiac magnetic resonance (CMR) imaging in interventional therapy of patients with acute myocardial infarction prior to and after treatment. Fifty-six cases of AMI patients with elective treatment by percutaneous coronary intervention (PCI) were continuously selected. Patients with an incidence of 7–10 days were treated with CMR and echocardiography to evaluate the quality of myocardial infarction, visual score method (VSM), wall motion score abnormality, left ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…Also, we found that wall motion score after revascularization has strong significant correlation with the occurrence of MACE like study made by Li, et al, [15] who found wall motion scores of the patients in the MACE group were significantly higher than the group without MACE.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Also, we found that wall motion score after revascularization has strong significant correlation with the occurrence of MACE like study made by Li, et al, [15] who found wall motion scores of the patients in the MACE group were significantly higher than the group without MACE.…”
Section: Discussionsupporting
confidence: 77%
“…These results are controversial with result by Li et al, [15] in their study. where fifty six patients with AMI with elective treatment by PCI were included, they found that the difference was of no statistical significance in the comparison of ECHO evaluation in LVEDD, LVESD, and LVEF prior to and following PCI.…”
Section: Discussionmentioning
confidence: 73%
“…The predictive ability of CMR in myocardial infarction (MI) is constantly being explored. At present, some studies have confirmed its role in AMI and other special types of myocardial infarction, such as unrecognized myocardial infarction (UMI) and myocardial infarction with nonobstructed coronaries (MINOCA) [ 63 , 64 , 65 , 66 ]. Recently, the CMR risk score was proposed for risk categorization in STEMI patients.…”
Section: Risk Scores For Specific Population or Including Special Ex...mentioning
confidence: 99%